2015
DOI: 10.1080/09583157.2015.1072130
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flowering calendula and cuphea plants onOrius insidiosussurvival and predation ofAphis glycines

Abstract: 2015): The effect of flowering calendula and cuphea plants on O. insidiosus survival and predation of Aphis glycines, Biocontrol Science and Technology, AbstractFlowering oilseed crops have the potential to diversify agroecosystems currently dominated by corn and soybeans and improve the provision of ecosystem services such as pest control. Nectar and pollen feeding may increase natural enemy fitness and searching behavior, increasing their survival and prey consumption rates. The soybean aphid (Aphis glycines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They may also provide shelter or reproductive sites for natural enemies and attract them through visual and olfactory cues, drawing them to suboptimal or disturbed environments such as crop fields (Beane & Bugg, ; Gurr et al., ; Perović et al., ; Zhao et al., ). Frequently used companion plants include marigold ( Calendula officinalis ; Martínez‐Uña, Martín, Fernández‐Quintanilla, & Dorado, ; Nemec, Beckendorf, Hesler, Riedell, & Lundgren, ; Zhao et al., ) and sweet alyssum ( Lobularia maritima ; Brennan, ; Gontijo, Beers, & Snyder, ). In those studies, these companion plants were considered as abundant pollen and nectar providers, and they mostly attracted hoverflies and hemipteran bugs, resulting in a successful control of arthropod pests.…”
Section: Introductionmentioning
confidence: 99%
“…They may also provide shelter or reproductive sites for natural enemies and attract them through visual and olfactory cues, drawing them to suboptimal or disturbed environments such as crop fields (Beane & Bugg, ; Gurr et al., ; Perović et al., ; Zhao et al., ). Frequently used companion plants include marigold ( Calendula officinalis ; Martínez‐Uña, Martín, Fernández‐Quintanilla, & Dorado, ; Nemec, Beckendorf, Hesler, Riedell, & Lundgren, ; Zhao et al., ) and sweet alyssum ( Lobularia maritima ; Brennan, ; Gontijo, Beers, & Snyder, ). In those studies, these companion plants were considered as abundant pollen and nectar providers, and they mostly attracted hoverflies and hemipteran bugs, resulting in a successful control of arthropod pests.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies regarding the effects of pesticides on beneficial species (Zhang & Sanderson 1990;Spollen & Isman 1996;Moscardini et al 2013;Garzón et al 2015;Nemec et al 2016). Most ones have focused on immediate and acute toxicity of pesticide but a few studies have demonstrated the relationship between pesticide residue and mortality of exposed beneficial arthropods (Bellows et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Cultivars with a low density and/or trichome length present an inadequate environment for the development of whiteflies, as this facilitates the eggs being blown away (Butter & Vir, 1989) or to get located more quickly by natural enemies (Riddick & Simmons, 2014;Nemec et al, 2016). However, trichomes are probably not the only characteristic responsible for the differences observed between cultivars, and further studies related to biochemical factors are necessary.…”
Section: Discussionmentioning
confidence: 99%